AR NATŪRALISTINIAI SOCIALINIAI MOKSLAI GALI BŪTI KRITINIAI? - Kirtiklis, Kęstas (Problems / Problemos, 2012)
The article deals with the conception of critical social sciences and their place in the wider context of methodological debates, particularly in the naturalism debate in contemporary philosophy of social sciences. The article analyzes two basic characteristics of critical social sciences -- methodological antinaturalism and critical axiological position. It is argued that because of excessively narrow notion of values (values as research-directing attitudes) implied by the critical axiological position philosophers of critical social sciences fail to demonstrate a necessary link between critical axiological attitude and particular methodology. Therefore, it is possible to relate critical axiology with naturalist as well as with interpretive methodology.